HELIUM DIFFUSION AND LOW-TEMPERATURE THERMOCHRONOMETRY OF APATITE - Wolf R.A.; Farley K.A.; Silver L.T. (My University, 1996)
To investigate the potential of the (U-Th)/He system for low-temperature thermochronometry, we have studied helium diffusion and have measured helium ages on Durango fluorapatite and on apatites from a gabbro and two tonalites from the Peninsular Ranges Batholith. Diffusivity at moderate to very low temperatures (as low as 80°C) was measured to high analytical precision using long duration incremental outgassing experiments. All four apatites displayed remarkably similar helium diffusion behavior. Helium loss apparently occurs via volume diffusion from subgrain domains (<60 µm) which are nearly identical in size all samples. at temperatures below 290°C, diffusivity obeys a highly linear Arrhenius relationship with an implied activation energy of about 36 kcal/mol. Above this temperature, diffusivity deviates from linearity toward lower activation energies. This transition does not arise from multiple diffusion domains, but rather from a reversible change in the physical mechanism of helium diffusion. For thermochronometric purposes the high-temperature diffusion behavior is largely irrelevant because essentially no helium is retained over geologic time at temperatures above 290°C. Using the results from the low-temperature regime, all samples yield helium closure temperatures in the range 75 +/- 7°C. This value is independent of chemical composition and grain size of the apatites, suggesting that a single closure temperature may apply to a wide range of samples. The (U-Th)/He ages of these apatites (17-120 Ma) range from a small fraction to nearly 100% of the crystallization age of their host rocks, and are consistent with a low-temperature thermochronometric interpretation. These results strongly support previous suggestions that (U-Th)/He dating of apatite can provide high precision chronometry of very low temperature geological events.